A framework for developing intelligent decision support systems using evolutionary fuzzy cognitive maps - Mateou, Nicos; Andreou, Andreas S. (My University, 2008)
This paper focuses on developing Intelligent Decision Support Systems within the framework of Genetically Evolved Fuzzy Cognitive Maps, thus at modelling real world problems and supporting the decision making process. The proposed framework is based on encoding experts' assessments on the nature of the problem under consideration. This assessment is inputted in a fuzzy knowledge base that uses a linguistic form following which it is modelled and processed by means of Fuzzy Cognitive Maps. The optimisation that follows with the help of Genetic Algorithms facilitates the simulation of hypothetical scenarios, while the defuzzification process implemented interprets the results along human reasoning lines. The effectiveness and reliability of the method proposed has been demonstrated by means of a case study on the Cyprus issue shortly before the April, 24 referendum.
Keywords: Genetic algorithms; Decision support systems; Expert systems; Fuzzy cognitive maps